Fire Regions as Environmental Niches: A New Paradigm to Define Potential Fire Regimes in Africa and Australia. Issue 8 (10th August 2022) - Zubkova, M.; Boschetti, L.; Abatzoglou, J. T.; Giglio, L.
Abstract: Despite the widespread use of the "fire regime" concept for describing spatial and temporal patterns and ecosystem impacts of fire, this concept lacks an unambiguous, quantitative definition. By adopting from the ecological literature the concept of climate niche, that is, the environmental conditions that allow a specie to exist, we propose a new framework where variables that promote fuel accumulation and desiccation were used to define the environmental space at the continental level, later divided into regions ("fire regions") with distinct fire potential. Our proposed approach emphasizes climate controls on fire patterns, distinct from the controls that humans exert on observed fire activity. By applying this framework, we identified nine fire regions in Africa and eight in Australia, distinguishing differences in fire patterns between continents as a result of changes in environmental gradient. Not only did we find that fire size and intensity varied significantly between continents, but biomes at a continental level were also found to be heterogeneous in terms of fire frequency, size, and intensity. For example, within African tropical savannas, the total annual rainfall and tree cover change drastically North and South of the equator, resulting in fire regions with significantly different fire characteristics. Meanwhile, in Australia, a strong gradient of annual temperature and precipitation seasonality was observed within tropical savannas and xeric shrublands, which was recognized by dividing those biomes into five regions with statistically different fire activity. Additionally, human presence led to some heterogeneity of fire patterns within delineated fire regions that also varied across biomes. Plain Language Summary: Fire is a natural component of most ecosystems that affects vegetation, soil, water, and the atmosphere. However, the ecosystem impacts of fire vary depending on fire characteristics, including fire size, intensity, and frequency. Here, we proposed a new approach for mapping "fire regions" with distinct patterns of fire activity based on environmental characteristics that promote or limit fuel accumulation and desiccation. We applied this method in Africa and Australia, the two most fire‐prone continents, to highlight similarities and distinguish differences in fire activity across continents. The latter were explained by differences in the gradients of those environmental characteristics. As a result, we identified nine fire regions in Africa and eight in Australia that were characterized by biophysical attributes (e.g., climate and vegetation cover) and fire patterns. Significantly, our approach identified regions with distinct fire attributes within individual biomes (most notably within tropical savannas and xeric shrublands) due to differences in environmental controls of fire activity. Our delineated fire regions can be used as a scale unit for fire‐statistics calculation and to analyze current fluctuation in fire activity within areas with somewhat homogeneous environmental conditions as a result of changes in human impact to improve our understanding of complex fire‐climate‐human relationships. Key Points: We present a new framework for defining regions (fire regions) with distinct fire‐potential based on environmental conditions Nine fire regions with significantly different fire characteristics were defined in Africa and eight in Australia Different fire patterns were detected within the same biome due to subtle changes in environmental gradient and level of human pressure